Home Health Care During Physical Distancing Affects Physical and Psychosocial Aspects, Self-Efficacy, Family Function, and Quality of Life of Families in Indonesia - Susanto, Tantut; Yunanto, Rismawan Adi; Septiyono, Eka Afdi; Deviantony, Fitrio (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Physical distancing during the COVID-19 pandemic has impacted the activities of daily living (ADLs) of families, such as physical and psychosocial aspects, self-efficacy, family social function, and overall quality of life. However, research investigating the effects of home health care in enhancing these aspects during the physical distancing period remains limited.Purpose: This study aimed to evaluate the effects of implementing home health care on physical and psychosocial aspects, self-efficacy, family social function, and quality of life of families in East Java Province, Indonesia.Methods: A quasi-experimental study was conducted among 768 healthy families that were purposively recruited from April to May 2020. The home health care program was implemented for one month to provide nursing care to the families. Data were collected using self-administered questionnaires, and SPSS software was employed for data analysis. Chi-square tests were applied for categorical variables, while paired t-tests were used for continuous variables.Results: Significant differences were observed in blood pressure, pulse, and temperature before and after the implementation of home health care during the physical distancing period (p<0.05). There was an increase in body mass index (23.29(5.59) vs. 23.78(7.53); p=0.001). Notably, significant differences were also found in COVID-19 exposure risk factors, personal risk factors, sleep patterns, and physical activity before and after home health care (p<0.05). Furthermore, improvements were noted in self-efficacy, family social function, and the quality of life of the families after one month of home health care (p<0.05).Conclusion: Home health care during physical distancing positively affected the physical and psychosocial aspects, self-efficacy, family social function, and quality of life of the families. Thus, the guidance and support offered through home health care should be further developed to help families navigate the “new normal” era of COVID-19.